Study on the Tribological Behavior of Laser Surface Texturing on Silicon Nitride Ceramic Under Water Lubrication - Hong-Jian Wang; Jing-De Huang; Bo Wang; Yang Zhang; Jin Wang (Lubricants)
The tribological behavior of silicon nitride (Si3N4) ceramic with textured patterns under water lubrication was investigated in this paper. Different textured patterns were fabricated using laser surface texturing (LST). Surface wettability was characterized by contact angle. The original surface and textured Si3N4 ceramic with triangular patterns presented as hydrophobic. However, the textured Si3N4 ceramic with hexagonal patterns presented as hydrophilic. Surface wettability and textured patterns were important factors affecting the friction performance of the Si3N4 ceramic. Our results indicated that symmetrical textured patterns were more beneficial for decreasing the coefficient of friction (COF) at lower reciprocating frequencies. In contrast, better surface wettability played a more important role in reducing the COF at higher reciprocating frequencies. The most severe damage observed on the untextured Si3N4 ceramic led to a higher wear rate. The symmetrical structure of hexagonal patterns was more conducive to decreasing the wear rate than triangular patterns. However, the Si3N4 ceramic with triangular patterns was more suitable for use at high-speed frictions due to better lubrication. The textured patterns had the function of storing lubricants and capturing and cutting debris. Thus, friction performance was improved by introducing textured patterns onto the surface of the Si3N4 ceramic. The friction and wear mechanisms are also discussed in this study.